PENGARUH KOMITMEN ORGANISASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA (Studi pada Koperasi Karyawan Kendali Harta PT Coca – Cola Amatil Indonesia, Central Java Semarang) (Students' Journal of Economic and Management, 2015)
Performance is the result of work in quality and quantity is achieved by a person in carrying out the tasks assigned to him in accordance with the standards or criteria have been established. Performance shows the success rate of employees in carrying out their duties and responsibilities, where the higher the performance of the employee, the productivity of the organization as a whole will increase. This study aimed to analyze the influence of organizational commitment, organizational culture influence on job satisfaction and organizational commitment, job satisfaction and organizational culture on employee performance Kopkar Kendali Harta PT. Coca -Cola Amatil Indonesia. The population in this study were all employees in the production of Kopkar Kendali Harta PT. Coca Cola Amatil Indonesia Central Java. A sample of 100 respondents was obtained by using purposive sampling method. This study uses multiple linear regression as data analysis tools. The results of this study indicate that the variable organizational commitment and organizational culture either partially or simultaneously positive and significant effect on organizational commitment. Other results showed variable organizational commitment, organizational culture and job satisfaction partially or simultaneously positive and significant impact on employee performance. From the test results obtained Adjusted R² value for equation 1 is equal to 0,579, so the influence of organizational culture variables and organizational commitment to job satisfaction is at 57.9%. In the second equation obtained Adjusted R² value of 0.574, so the influence of organizational commitment, organizational culture and job satisfaction on the performance of employees is 57.4. Keywords: organizational commitment, organizational culture, job satisfaction, employee performance